The Effect of Financial Literacy and Religiosity on Investment Decisions in the Stock Market - Siska Yuli Anita; Fadzila Azni Ahmad (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Financial literacy is vital for the millennial generation of investors to manage personal finances effectively and secure long-term economic stability. This study investigates the effect of financial literacy and religiosity on the investment decision in the stock market of the millennial generation in Bandar Lampung City. Using a quantitative descriptive approach, 96 millennial generation investors were selected through purposive sampling, and data were collected via questionnaires. SmartPLS 4 was employed to test validity, reliability, and hypotheses. Results indicate that both financial literacy and religiosity significantly influence investment decisions on the stock market. Financial literacy contributes 65.2% (p = 0.002 < 0.05), while religiosity shows a stronger effect of 63.9% (p = 0.001 < 0.05). Together, the two variables explain 65.2% of the variance in stock market investment decisions among the millennial generation, indicating a strong explanatory power of the research model. These findings suggest that while financial literacy enhances investors’ technical ability to evaluate and manage investments, religiosity plays a crucial role in shaping ethical considerations, risk awareness, and long-term investment orientation. The study highlights the importance of integrating financial literacy and religiosity for more rational, ethical, and sustainable investment behavior among millennial investors, particularly in Indonesian stock markets.